Survey of the awareness of xerostomia in elderly - Md Ismail, Nur Adlina Diyana; Fitriana, Elizabeth; Tjahajawati, Sri (Universitas Padjadjaran, 2015)
Introduction: One of the significant public health issues in this modern time is the rapidly escalating elderly popula-tion. The number of people older than 65 years will double to 14% of the world’s population in the next 30 years. Due to various chronic conditions as well as prescription medications, it is presumed that more than 30% of the population aged 65 years and older is experiencing xerostomia, a condition not well known among the elderly. This study was not focusing on the disease per se but aimed to evaluate the awareness of the condition. Methods: The method of this study was descriptive with the survey method. Questionnaires were given to a sample gathered consecutively in the period of one month. The results were then presented in table form. Results: Out of the 63 respondents, 15.9% were considered to have full awareness of this condition. 44.4% of respondents were in the moderate awareness category, and 39.7% were not aware of the disease. Conclusion: Majority of the elderly have a moderate level of awareness towards xerostomia.